The Development of the Arabic Lexicon in the Digital Age : A Study of Neologisms and Loanwords - Sahidah, Novita Sahidah (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The development of digital technology has resulted in significant changes in language dynamics, including Arabic, which has experienced vocabulary additions through numerous neologisms and new loanwords. This study aims to analyze the form, creation process, and role of new lexicons in Arabic in the digital age. This study uses an analytical-descriptive approach with qualitative methods. Data were obtained from various digital sources, including social media, online news sites, and Arabic-language digital communication platforms. Data were collected through text observation and documentation, while data analysis was carried out through a process of data selection, categorization, and linguistic opinion based on morphological and semantic studies. The results reveal that the evolution of the Arabic lexicon in the digital age is characterized by three main aspects: the creation of neologisms through internal Arabic derivation, phonological and morphological adjustments to foreign words, and the application of direct transliteration from various languages, especially English. This phenomenon indicates a relationship between the structure of classical Arabic and the demands of modern, global and rapid communication such as technology. This study emphasizes that advances in the digital lexicon not only increase the Arabic vocabulary but also reflect social, cultural, and technological representations among its speakers. This research is expected to facilitate understanding of the dynamics of Arabic lexicon development in the digital era, especially as it relates to the study of neologisms and loanwords.   Keywords: lexicon, digital era, neologism study, loanwords